Theoretical evaluation of integrated Basin at Risk (iBAR) method for international water conflict-cooperation analysis - Seyedeh Simin Mirhashemi Dehkordi; Hojjat Mianabadi; Saeed Bagherzadeh; Ebrahim Hajiani; Seyed Jalal Dehghani Firouzabadi (Frontiers in Water, 2024)
Comprehensive analysis of water interactions enhances understanding of the dynamic and complex conditions in transboundary river basins. The Basin at Risk (BAR) method is among common methods to analyze water interactions. The integrated Basin at Risk (iBAR) method has recently enhanced BAR. As an extension of BAR, iBAR emphasizes hidden drivers of water conflict and cooperation, whereas BAR includes visible ones. The novelty of iBAR is grounded in Johan Galtung’s theory of violence and the concept of positive peace. This method emphasizes the importance of capturing the hidden aspects of water conflicts as well as the concept of positive peace in water interactions. While iBAR has made significant improvements in addressing water conflicts, some challenges remain. This paper provides a review and theoretical analysis of iBAR. Initially, the iBAR development phases are reviewed in terms of positive peace conceptualization and contextualization in water interactions. Following this, the theoretical background of this method is discussed. The results suggest that the iBAR method could be further enhanced by revising concepts of positive peace, social justice, and environmental justice in water interactions.